Improved H2/H∞ control-based robust PI controller design of SMES for suppression of power fluctuation in microgrid - Vachirasricirikul, Sitthidet; Ngamroo, Issarachai (My University, 2014)
In the microgrid integrated with the renewable energy sources such as wind power and photovoltaic, the random power productions from such renewable sources may cause the severe power fluctuation problem. This paper focuses on a robust controller design of a superconducting magnetic energy storage (SMES) for stabilizing the power fluctuation in a microgrid. The proportional-integral (PI)-based damping controllers for active and reactive power control of SMES are optimally tuned based on the improved H2/H∞ control with the automatic selection of the reference input. The particle swarm optimization is applied to achieve the optimal PI parameters automatically. Simulation results show that the power fluctuation from the renewable sources is greatly damped by robust SMES controller.
Keywords: Microgrid; mixed H2/H∞ control; particle swarm optimization; renewable energy sources; superconducting magnetic energy storage